Strategi Peningkatan Kesadaran Merek UMKM di Desa Kedungjambe melalui Pemasaran Digital - Faridatun Nikmah; Maharani Ikaningtyas (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
This study aims to increase brand awareness of Micro, Small, and Medium Enterprises (MSMEs) in Kedungjambe Village by optimizing the use of WhatsApp Business and the Shopee e-commerce platform. The main problem faced by MSMEs is low competitiveness due to lack of visibility among consumers. The proposed solution includes training in digital marketing strategies with a focus on managing WhatsApp Business accounts for more effective communication with customers, as well as utilizing Shopee features to expand the market. MSME actors were given training in creating attractive promotional content on WhatsApp Business, using broadcast features for direct interaction, and managing online stores on Shopee, including optimizing product descriptions, stock management, and sales analysis. In addition, a simulation of utilizing Shopee as a strategic sales channel was also carried out to strengthen the marketing experience. The results of this activity showed a significant increase in brand awareness, the number of customers connected via WhatsApp Business, and sales volume on Shopee for participating MSMEs.